Rasagiline as Adjunct to Levodopa for Treatment of Parkinson's Disease: A Systematic Review and Meta-Analysis. (30th August 2022) - Kano, Osamu; Tsuda, Hiroshi; Hayashi, Ayako; Arai, Masaki
Abstract : Background . Rasagiline is a selective, irreversible monoamine oxidase type B inhibitor used as monotherapy in early Parkinson's disease and as an adjunct therapy to levodopa in Parkinson's disease with motor fluctuations. Objectives . This meta-analysis aimed to provide updated evidence on the efficacy for motor and nonmotor symptoms and the safety of rasagiline/levodopa versus levodopa in patients with Parkinson's disease experiencing motor fluctuations. Methods . A systematic literature search was conducted (January 18-19, 2021) using PubMed, Cochrane Library, EMBASE, Web of Science, and Google Scholar to identify randomized controlled trials comparing rasagiline/levodopa versus placebo/levodopa in patients with Parkinson's disease experiencing motor fluctuations. Outcomes included change in wearing-off time, Unified Parkinson's Disease Rating Scale (UPDRS)/Movement Disorder Society-UPDRS (MDS-UPDRS) II and III scores, treatment-emergent adverse events (TEAEs), and Parkinson's Disease Questionnaire (PDQ-39) summary index score. A random effect model was used to estimate the treatment effects. Results . Six studies were included (1912 patients). Significant improvements in wearing-off time (standardized mean difference [SMD]: −0.50, 95% confidence interval [CI]: –0.92 to –0.09, p = 0.002 ), levodopa dosage (SMD: −0.18, 95% CI: −0.35 to –0.01, p = 0.041 ), UPDRS/MDS-UPDRS II (SMD: −0.39, 95% CI: −0.52 to –0.25, p < 0.0001 ), UPDRS/MDS-UPDRS III (SMD: −0.30, 95% CI: −0.44 to –0.16, p < 0.0001 ), and PDQ-39 summary index score (SMD: –0.21, 95% CI: –0.37 to –0.04, p = 0.013 ) were observed with rasagiline/levodopa versus placebo/levodopa. The incidence of TEAEs did not differ between treatments (risk ratio: 1.13, 95% CI: 0.98–1.30, p = 0.093 ). Conclusions . This meta-analysis further indicated the superiority of rasagiline/levodopa in improving motor and nonmotor symptoms of Parkinson's disease, with a similar safety profile to that of levodopa in Parkinson's disease with motor fluctuations.